A Prospective Cross-Sectional Analysis of Construct Validity for the PALMPASS, A Brief Patient-Reported Outcome Measure for Psoriasis. Issue 4 (October 2019) - Farahi, Jessica M.; Lynn, Darren; Anand, Pratibha; Walsh, Jessica A.; Hashim, Mena; Duong, Ryan; Dellavalle, Robert P.; Reimold, Andreas; Kerr, Gail S.; Richards, John S.; Chang, Elizabeth; Kaushik, Prashant; et al.
Background: While the Psoriasis Area and Severity Index (PASI) represents the most commonly used assessment tool for psoriasis severity, it has been criticized for its complexity in clinical practice. Objective: To validate a simplified 2-item patient-administered limited measure psoriasis area and severity score (PALMPASS) compared to standardized measure of psoriasis. Materials and Methods: This was a prospective observational survey of adult patients with psoriasis and psoriatic arthritis in Veterans Affairs Medical Center (VAMC) dermatology and rheumatology clinics participating in the Program to Understand the Longterm outcomes in SpondyloARthritis registry between January and June 2016 (n = 885). Patients at 7 US VAMCs (n = 363) completed a 2-item, 11-point PALMPASS questionnaire, assessing (1) how psoriasis affected the patient and (2) the degree of surface area involvement. Results from the PALMPASS were then compared to the PASI, the Psoriasis Symptom Inventory (PSI) and the Dermatology Life Quality Index (DLQI). Data were analyzed using Lin concordance, intraclass correlations, Spearman correlations, and linear regression. Results: Strong correlations existed between PALMPASS and PASI (Spearman ρ = 0.74, P < .001), PSI (Spearman ρ = 0.71, P = .001), and DLQI (Spearman ρ = 0.77, P < .001). Results were comparable in analyses based on intraclass correlations. Elevated C-reactive protein concentrations correlated with higher PALMPASS. Conclusion: The PALMPASS is a patient-reported instrument that demonstrates validity and serves as a reliable and simplified tool to guide evidence-based management.